KONSEP PEMILIHAN VEGETASI LANSEKAP PADA TAMAN LINGKUNGAN DI BUNDERAN WARU SURABAYA - Hendra Kurniawan; Rizki Alfian (BUANA SAINS, 2010)
Circle of Waru represent green open space area with storey level of polutan dirt (PM 10) and Nitrogen oxide ( NOX) exceed standard due to high vehicle activity and quality trigger the existence of storey with level of polutan able to endanger health of human being. This research was conducted during 6 month. Location of the research is in Circle of Waru Surabaya, which located in Countryside Hamlet Mussel Singularity, District of Gayungan, Town of Surabaya and cowered area 35.000 m2, mean air temperature 28-34ºC and Laboratory/Studio Architecture Map University of Tribhuwana Tunggadewi. The result of this research, can be concluded that Town of Surabaya with storey level of actifity high vehicle that is: 4.164/hour, caused the condition of air of NOx and dirt have exceeded standard boundary lower quality, it is mean that area condition is impure to overcome problems of environment planning of settlement area is needed for Require To Be Green Open Space by selected of functional crop type and settlement of crop with high rise system, that is using birch crop, ground cover and clump